Will Climate Change Alter the Swimming Behavior of Larval Stone Crabs?: A Guided-Inquiry Lesson - Abigail L. Smith; Jessyca LaBadie; Aly Busse; Emilie Solomon; Casie Farrell; Daniel M. Holstein; Zuo George Xue; Philip M. Gravinese (Current: The Journal of Marine Education)
The ocean has absorbed ~one third of the excess atmospheric carbon dioxide (CO2) released since the Industrial Revolution. When the ocean absorbs excess CO2, a series of chemical reactions occur that result in a reduction in seawater pH, a process called ocean acidification. The excess atmospheric CO2 is also resulting in warmer seawater temperatures. These stressors pose a threat to marine organisms, especially during earlier life stages (i.e., larvae). The larvae of species like the Florida stone crab (Menippe mercenaria) are free swimming, allowing a population to disperse and recruit into new habitats. After release, stone crab larvae undergo vertical swimming excursions in response to abiotic stimuli (gravity, light, pressure) allowing them to control their depth. Typically, newly hatched larvae respond to abiotic cues that would promote a shallower depth distribution, where surface currents can transport them offshore to complete development. As larvae develop offshore, they become less sensitive to certain abiotic stimuli, which promotes a deeper depth distribution that may expose them to variable current speeds, thus influencing the direction of advection (horizontal movement). Environmental stressors like ocean acidification and elevated seawater temperatures may also impact the larvae’s natural response to these abiotic stimuli throughout ontogeny (development). Changes in their natural swimming behavior due to climate stressors could, therefore, influence the transport and dispersal of the species. This guided-inquiry lesson challenges introductory marine biology and oceanography students to determine how future ocean pH and temperature projections could impact the swimming behavior of Florida stone crab larvae.